2D Direction of Arrival Estimation for Cross Array in the Presence of Mutual Coupling. (4th March 2014) - Hu, Weiwei; Zhang, Aijun; Wang, Changming
Abstract : This paper proposes a new method for cross array to estimate two-dimensional direction of arrival (2-D DOA) in the presence of mutual coupling. In this method, the array elements which are affected by the same mutual coupling are chosen on x -axis and z -axis, respectively. Then a new matrix is constructed with the proper entries of cross covariance matrix of the chosen elements outputs on x -axis and z -axis. Propagation method (PM) and rotational invariance techniques for uniform linear array (ULA) are utilized in the constructed matrix to obtain two parameters correlated with elevations and azimuths. While calculating and pairing the two parameters, only once eigendecomposing and several division operations are required with the relationship among the matrix, its eigenvalues, and corresponding eigenvectors. Simulations are presented to validate the performance of the proposed method.